PERAN GURU DALAM UPAYA MENINGKATKAN KEEFEKTIFAN PEMBELAJARAN PKN DI SEKOLAH DASAR - Ade Kurnia Sari; Amelia Alifah Sagala; Putri Rahmadani Harahap; Maria Febrina Sianturi (JURNAL ILMIAH NUSANTARA, 2024)
Citizenship Education (PKN) in elementary schools has an important role in forming children's character and civic awareness. The teacher's role in the effectiveness of PKN learning is very vital. PKN teachers are expected to be able to develop learning methods that are interesting and relevant to children's daily lives, so that they can understand civic values ​​better. Apart from that, teachers also have a role as role models in implementing civic values ​​in everyday life. By providing good examples, teachers can shape children's character to be better and have the awareness to contribute to the development of the country. However, the challenges in teaching PKN in elementary schools are also not small. Communication skills and the right approach are needed so that PKN material can be delivered well and is easily understood by children. Apart from that, teachers also need to keep up with the times and utilize technology in PKN learning. In facing these various challenges, PKN teachers are expected to continue to improve their competence and professionalism through various training and self-development, so that they can make maximum contributions in building the character and citizenship awareness of children in elementary schools.